Modeling Longshore Sediment Transport for Sustainable Coastal Management in the Damietta Port Area - Ahmed S.A. Ibrahim; Anas M. El Molla; Hany G. I. Ahmed (Journal of Eta Maritime Science, 2024)
Within the framework of constructing mega coastal ports in Egypt, this research aims to achieve coastal management sustainability in its surroundings by modeling the Longshore Sediment Transport 'LST'. The literature in the fields of modeling and sediment transport was reviewed and scrutinized. The model was calibrated by contrasting the calculated wave data against 2003 measured data at the Damietta Buoy. The model inputs were tuned to produce a result that was similar to the observed data. Moreover, the model results were validated against 2005 measured data at the Damietta Buoy. Likewise, MIKE21 SM was used to estimate 2011 bed levels within Damietta Port, where 2010 bathymetrical survey data were used. Confident with the model results, it was employed to synthesize transport data for 1940-2020 in terms of LST, Gross LST 'GLST' and Net LST 'NLST' while considering human intervention and implementing ERA5 wave data. Results were obtained and analyzed, and there was a significant correlation between the significant wave height 'Hs' and the wave period 'Tp' and GLST (i.e. R=0.91-0.79, respectively). The analyzed trend results highlighted that in the pre-construction phase of Damietta Port, increases in GLST and NLST were modest (1139.9 and 243.7 m3/year, respectively). However, in the post-construction phase of Damietta Port, they escalated between 4679.47 and 3962 m3/year. The analyzed results indicated that after introducing coastal protection, GLST and NLST decreased to 2978.1 and 2176 m3/year, respectively.